Theoretical insights into homogeneous catalysis impact on ion transfer-electron transfer coupled processes at thick-film modified electrodes - Fernández, R. A. (2024)
Factor de Impacto: 4.1 Source Elsevier: What are journal pre-proofs? “Journal pre-proofs are Articles in Press that have been peer reviewed and accepted for publication by the Editorial Board of this publication. They have undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but are not yet definitive versions of record. These versions will undergo additional copyediting, typesetting and review, and may not yet have full ScienceDirect functionality. For example, supplementary files may still need to be added, links to references may not resolve yet, etc. The text could still change before final publication. Although journal pre-proofs do not have all bibliographic details available yet, they can be cited using the year of online publication and the DOI, as follows: author(s), article title, Publication (year), DOI. Please consult the journal’s reference style for the exact appearance of these elements, abbreviation of journal names, and use of punctuation. When the final article is assigned to a volume/issue of the publication, the Article in Press version will be removed and the final version will appear in the associated published volumes/issues of the publication. The date the article was first made available online will be carried over”. Fuente: Elsevier: ¿Qué son las pruebas previas de revistas? “Las pruebas previas de la revista son artículos de prensa que han sido revisados por pares y aceptados para su publicación por el consejo editorial de esta publicación. Han sufrido mejoras después de su aceptación, como la adición de una portada y metadatos, y formato para facilitar la lectura, pero aún no son versiones definitivas del registro. Estas versiones se someterán a edición, composición tipográfica y revisión adicionales, y es posible que aún no tengan la funcionalidad completa de ScienceDirect. Por ejemplo, es posible que aún sea necesario agregar archivos complementarios, que los enlaces a las referencias aún no se resuelvan, etc. El texto aún podría cambiar antes de la publicación final. Aunque las pruebas previas de revistas aún no tienen todos los detalles bibliográficos disponibles, se pueden citar utilizando el año de publicación en línea y el DOI, de la siguiente manera: autor(es), título del artículo, Publicación (año), DOI. Consulte el estilo de referencia de la revista para conocer la apariencia exacta de estos elementos, la abreviatura de los nombres de las revistas y el uso de la puntuación. Cuando el artículo final se asigna a un volumen/número de la publicación, la versión Artículo en prensa se eliminará y la versión final aparecerá en los volúmenes/números publicados asociados de la publicación. Se trasladará la fecha en que el artículo estuvo disponible en línea por primera vez”. Elsevier [Commercial Publisher]